An update on the conquests and perspectives of cardio-oncology in the field of tumor angiogenesis-targeting TKI-based therapy. Issue 6 (3rd June 2019) - Galvano, Antonio; Guarini, Aurelia; Iacono, Federica; Castiglia, Marta; Rizzo, Sergio; Tarantini, Luigi; Gori, Stefania; Novo, Giuseppina; Bazan, Viviana; Russo, Antonio
ABSTRACT: Introduction : The angiogenesis mechanism is considered a crucial point in neoplastic development. A growing number of multi-targeted tyrosine kinase inhibitors (TKI) has been developed and approved for cancer treatment during the last few years. Cardiac side effects still remain an issue to manage nowadays. These drugs mechanisms and toxicities have already been discussed, hence the authors will report updates on these already available drugs. Area covered : This manuscript provides an updated review on the new mechanisms involved in angiogenesis and cardiotoxicity that are TKI-related. Here is reported an overview of the already available and the most recent TKIs under investigation in the oncology field. A literature review has been performed, focusing on the most relevant phase II and phase III trial results. Expert opinion : TKIs represent a new and important resource in the oncology field. Since the use and the number of VEGFR-TKI is constantly increasing, a specific focus on cardiotoxicity development and management appears as justified. Oncologists must record cardiovascular risk factors at baseline in order to stratify patients' risk before undergoing TKI-VEGFRs. A collaboration between oncologists and cardio-oncologists is strongly recommended to earlier manage cardiovascular events (i.e. arterial hypertension) that could interfere with oncological results.